2008
DOI: 10.1111/j.1440-1746.2007.05080.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional and morphological alterations in small intestine mucosa of chronic alcoholics

Abstract: The study brought out the changes in small bowel of chronic alcoholics having ALD at both cellular and subcellular levels which correlated significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 24 publications
(27 reference statements)
1
37
0
4
Order By: Relevance
“…These results suggest that chronical alcohol consumption could induce IEB disruption, which is consistent with previous studies (Banan, Choudhary, Zhang, Fields, & Keshavarzian, 1999;Zhang, Hu, Yuan, & Wu, 2009;Zhong et al, 2010). Although alcohol exposure can cause gut leakiness, as demonstrated by detection of intestinal barrier dysfunction, previous light-microscopy studies found that chronic alcohol exposure did not affect intestinal histology (Bhonchal et al, 2008). There was also no obvious difference in intestinal histology between the alcoholfed mice and the control mice in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…These results suggest that chronical alcohol consumption could induce IEB disruption, which is consistent with previous studies (Banan, Choudhary, Zhang, Fields, & Keshavarzian, 1999;Zhang, Hu, Yuan, & Wu, 2009;Zhong et al, 2010). Although alcohol exposure can cause gut leakiness, as demonstrated by detection of intestinal barrier dysfunction, previous light-microscopy studies found that chronic alcohol exposure did not affect intestinal histology (Bhonchal et al, 2008). There was also no obvious difference in intestinal histology between the alcoholfed mice and the control mice in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Either loss of the epithelial cells or disruption of the tight junctions will lead to an increase in intestinal permeability. Clinical studies demonstrated that acute alcohol administration can cause apparent histopathological changes in the proximal part of the small intestine, whereas chronic alcohol consumption only induces minor histopathological changes (9,12,34). Our previous study (30) also showed that intestinal histopathological alterations, such as loss of epithelial cells at the top of the intestinal villi, were associated with acute alcohol intoxication-induced intestinal barrier disruption in mice (30).…”
Section: Discussionmentioning
confidence: 83%
“…Kapszulaendoszkópián átesett májcirrhosisos betegek kétharmadában találtak gyulladásos nyálkahár-tya-eltéréseket [31]. Továbbá különféle morfológiai elváltozások is leírásra kerültek a vékonybélben, mint pél-dául részleges boholyatrophia, enyhe-közepes fokú lamina propria sejtes infi ltráció és intraepithelialis lymphocytaszaporulat [32]. A bélbarrier integritásának károsodásáért a nyálkahártya vérátáramlásának megvál-tozása, az oxidatív stressz, a megnövekedett proinfl ammatorikus citokinkoncentráció és a nitrogén-oxid felelő-sek elsősorban [33,34].…”
Section: Coeliakia Morbus Crohn Májcirrhosisunclassified